The Influence of wine storytelling on the global wine tourism experience - Vasco Santos; Álvaro Lopes Dias; Paulo Ramos; Arlindo Madeira; Bruno Sousa (Wine Economics and Policy, 2022)
The aim of this paper is to evaluate the role of wine storytelling as an antecedent in the wine tourism experience, namely on other constructs such as winescape attributes, sensorial attraction, wine excitement and cultural experience. This study analyses the combined use of five wine tourism experience dimensions as well the influence of storytelling as a key antecedent of the wine experience. This study extends existing knowledge by identifying new key drivers which focus on wine tourist behavioural responses within visits to the wine cellars. Data were collected within two wine tourism settings in Madeira and Porto wine cellars, from two convenience samples of 647 international wine tourists. Using partial least square structural equation modeling, the results show a direct impact of wine storytelling on the wine tourism experiences of wine tourists, through winescape attributes and sensorial attraction, that also act as mediators, with wine excitement and cultural experience as the outcomes of the visit/tasting.
Keywords: 330; cultural experience; sensorial attraction; wine excitement; wine storytelling; wine tourism; winescape attributes